Analisis Faktor-Faktor yang Memengaruhi Kepatuhan Tenaga Kesehatan dalam Pengisian Rekam Medis Elektronik di Rumah Sakit Swasta Tipe B Jakarta Utara - Sulvi Anggraini; Yeny Sulistyowati; Tinon Ambarini (Lembaga Pengembangan Kinerja Dosen, 2025)
Electronic Medical Records (EMR) are crucial for the quality of healthcare services, but compliance remains a challenge. This study analyzed factors influencing compliance among healthcare workers at a type B private hospital in North Jakarta using a quantitative cross-sectional design with 58 respondents through total sampling. Data were obtained through questionnaires related to individual factors (age, length of service, knowledge), psychological factors (attitude, motivation), and organizational factors (leadership, work design, rewards). The results showed that 72.4% of respondents were compliant. The chi-square test revealed a significant relationship between compliance and age (p=0.042), length of service (p=0.000), knowledge (p=0.001), attitude (p=0.017), motivation (p=0.002), leadership (p=0.046), and rewards (p=0.010), while work design was not significant (p>0.05). Multivariate analysis found age, length of service, knowledge, and leadership as the dominant factors. Healthcare workers with younger age, shorter tenure, good knowledge, positive attitudes, high motivation, good leadership, supportive work designs, and adequate reward systems tend to have higher compliance rates. Improving compliance in completing EMRs depends not only on individual factors but also requires organizational support through effective leadership and management systems. Recommended interventions include improving digital literacy, regular training, strengthening a work culture that emphasizes the importance of medical documentation, and implementing peer learning strategies among healthcare workers to accelerate adaptation and share best practices in completing EMRs.